SURVEI MINAT DAN MOTIVASI PESERTA SENAM AEROBIK DI SANGGAR SENAM ULAK PATIAN - Rana Sari; Lolia Manurizal; Resdianto (JURNAL ILMIAH PENJAS (Penelitian, Pendidikan dan Pengajaran), 2026)
This study aims to determine the level of interest and motivation of participants in aerobic exercise activities at the Ulak Patian Fitness Studio. The research used a quantitative approach with a descriptive survey method. The population consisted of all active aerobic exercise participants at the Ulak Patian Fitness Studio, with a total sample of 10 respondents selected using total sampling technique. The research instrument was a questionnaire using a Likert scale that had been tested for validity and reliability. Data were analyzed using descriptive statistics in the form of mean scores and percentages. The results showed that the participants’ interest level in aerobic exercise was categorized as highly interested with an average score of 3.7. The highest interest dimension was found in the social and functional aspects with a score of 3.9, indicating that participants joined aerobic exercise to gain health benefits and social interaction. Meanwhile, the motivation level of participants was categorized as very high with an average score of 3.9, where intrinsic motivation became the dominant factor. The indicator of enjoyment and satisfaction obtained the highest score of 4.0. These findings indicate that participation in aerobic exercise is influenced by awareness of health benefits and enjoyable exercise experiences that can increase community participation in sports activities.